1993
DOI: 10.1002/jbm.820271211
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of extruded collagen fibers for ACL reconstruction

Abstract: Collagen fibers used in a scaffolding device for ligament reconstruction must be thin, strong, and degradable. The purpose of this study was to determine the effects of fiber diameter (20, 50, or 90 microns), crosslinking agent (uncrosslinked, dehydrothermal-cyanamide, or glutaraldehyde), and hydration on the initial mechanical properties, biocompatibility, and subcutaneous degradation rates of fibers extruded from an acidic dispersion of insoluble type I collagen. The wet tensile strength of extruded collagen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
90
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(96 citation statements)
references
References 13 publications
6
90
0
Order By: Relevance
“…Previously, animal implant studies showed that insoluble collagen threads, crosslinked with a combination of DHT and EDC treatments, facilitated better scaffold degradation and tissue ingrowth properties than either crosslinking technique alone. 46,47 The results of our in vitro studies are consistent with these findings and suggest that the next generation of self-assembled collagen threads should be crosslinked with a physical crosslinking technique such as DHT treatment to mechanically stabilize the scaffolds and EDC crosslinking to facilitate cell migration and new tissue regeneration.…”
Section: Discussionsupporting
confidence: 89%
“…Previously, animal implant studies showed that insoluble collagen threads, crosslinked with a combination of DHT and EDC treatments, facilitated better scaffold degradation and tissue ingrowth properties than either crosslinking technique alone. 46,47 The results of our in vitro studies are consistent with these findings and suggest that the next generation of self-assembled collagen threads should be crosslinked with a physical crosslinking technique such as DHT treatment to mechanically stabilize the scaffolds and EDC crosslinking to facilitate cell migration and new tissue regeneration.…”
Section: Discussionsupporting
confidence: 89%
“…Similar stress-strain curves have also been reported previously for collagenbased biomaterials [57][58][59][60][61][62][63][64] and nano-fibrous meshes [65][66][67]. Most important of all, the electro-spun mats produced in this study were characterised by mechanical properties that closely match those of native tissues, such as anterior cruciate ligament, Achilles tendon and skin and implantable devices [30,62,[68][69][70][71][72][73][74][75].…”
Section: Discussionsupporting
confidence: 83%
“…Few attempts at creating a bioengineered ACL (bACL) have been reported (Dunn et al 1992(Dunn et al , 1993(Dunn et al , 1994. A drawback of Dunn's approach (Dunn et al 1994) is that the matrix of the graft cannot be quickly degraded, and its remodelling is impaired.…”
Section: Introductionmentioning
confidence: 99%